Knowledge and Practice on Maternal Health Care among Badi Women - Nepali, Purna Bahadur (Journal of Gurubaba, 2025)
Maternal health care is one of the major and important components of reproductive health. No can become healthy without safe motherhood. This study was carried out in ward number one of the Birendranagar Municipality of Surkhet district. In this study the objective of this study is to identify the knowledge and practice as well as relation between them of Badi mothers on maternal health care. This study is based on descriptive type of research design and it is quantitative in nature. To select respondents census method was applied. Interview schedule was used as main tool of data collection and data were collected by researcher by visiting door to door. Collected data were analyzed by the help of mathematical numerical.Among the total respondents 28 percent of the respondents had done minimum four ANC visit during pregnancy, 45.33 percent of the respondents had face problems during pregnancy like headache, blurring vision, tiredness and bleeding. 29.33 percent of the respondents had not taken TT immunization during pregnancy. About 74.67 percent of the respondents were delivered at home where as 67.85 percent of the respondents were delivered with the help of experienced relatives at home delivery. 37.85 percent of the respondents who were deliver at home were suffered from different kinds of health problems like bleeding, obstructions and prolonged labour. Most of the respondents had not got health checkup during postnatal period. The respondents who were delivered at hospital had taken vitamin A during postnatal period where as 44.65 percent respondents who were delivered at home had taken vitamin A during postnatal period. About 96 percent of the respondents had feed colostrum's to their newborn baby.